2020
DOI: 10.3390/su12229600
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Ditch Berm Delineation Using Lidar Data: A Case Study of Waseca County, Minnesota

Abstract: Within a drainage system, drainage ditches are designed to improve existing natural drainage. Although drainage ditches are mostly engineered, they can also be part of natural watercourses. For environmental sustainability, in many places there are guidelines to establish vegetative buffer strips along the boundary of drainage ditches. In this landscape planning study, a geospatial modeling framework was established to identify these drainage system landforms and the boundary that separates these landforms fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We demonstrate that our approach of combining deep learning with high-density ALS data to map drainage ditches has accuracy equal to or higher than that of previous studies. However, the studies by Graves et al (2020), Kiss et al (2015), Larson andTrivedi (2011), Rapinel et al (2015), Stanislawski et al (2018) reported only recall, which made them difficult to evaluate. Additional metrics on false positives would be helpful for a comparison with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that our approach of combining deep learning with high-density ALS data to map drainage ditches has accuracy equal to or higher than that of previous studies. However, the studies by Graves et al (2020), Kiss et al (2015), Larson andTrivedi (2011), Rapinel et al (2015), Stanislawski et al (2018) reported only recall, which made them difficult to evaluate. Additional metrics on false positives would be helpful for a comparison with our results.…”
Section: Discussionmentioning
confidence: 99%